RELASI KUASA PADA PERNIKAHAN POLIGAMI DALAM PERSPEKTIF KEKERASAN SIMBOLIK - Maulana Hazmi (Saskara : Indonesian Journal of Society Studies, 2021)
This research is based on the researcher's interest in how the relationship between men and women in polygamous marriages. This study aims to describe what makes women willing to be polygamous and what kind of relationship exists between husband and wife in a polygamous family. This research uses a qualitative approach with a case study method. Data collection techniques used are through observation techniques, in-depth interviews, documentation and literature study on related documents. The results showed that in a polygamous family there is a discourse battle, this discourse battle is won by the husband, so that the husband has the right to determine the values ​​used in the family. In polygamous marriages, religion is used and believed to be the dominant discourse. Capital accumulation also affects the position of husband and wife in the family, including economic, social, cultural and symbolic capital. This form of domination carried out by the husband and not being aware of the domination by the wife who works subtly is called by Bourdieu as a form of symbolic violence.